2013
DOI: 10.1007/s10549-013-2521-2
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and breast cancer survival: a report from the Shanghai Breast Cancer Survival Study

Abstract: BACKGROUND We investigated the association of major comorbidities with breast cancer outcomes using the Shanghai Breast Cancer Survival Study, a population-based, prospective cohort study of Chinese women diagnosed with breast cancer. METHODS Analyses included 4,664 women diagnosed with stage I-III incident breast cancer aged 20–75 years (median age=51) during 2002–2006. Women were interviewed at 3–11 months post-diagnosis (median=6.4) and followed up by in-person interviews and linkage with the vital statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 39 publications
(59 reference statements)
4
45
2
Order By: Relevance
“…Similarly, other studies have reported diabetes mellitus in 6.2 28 , 8 11 and 9% 14 of BCS. In the SBCS study, diabetes was associated with a 40% higher risk of total mortality and death unrelated to breast cancer, but not breast cancer-specific mortality 28 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similarly, other studies have reported diabetes mellitus in 6.2 28 , 8 11 and 9% 14 of BCS. In the SBCS study, diabetes was associated with a 40% higher risk of total mortality and death unrelated to breast cancer, but not breast cancer-specific mortality 28 .…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, other studies have reported diabetes mellitus in 6.2 28 , 8 11 and 9% 14 of BCS. In the SBCS study, diabetes was associated with a 40% higher risk of total mortality and death unrelated to breast cancer, but not breast cancer-specific mortality 28 . In another study of BCS, diabetes was associated with a 39% increased risk of all-cause mortality, similar to rates observed in diabetics without breast cancer 30 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Breast cancer patients with a history of cardio-vascular disease experienced elevated overall mortality in two cancer registry-based studies (1, 16) and elevated breast cancer-specific mortality in another study (20), but not in two smaller, non-cancer registry-based studies (18, 19). As noted above, the omission of radiotherapy may have adverse effects on recurrence rates and overall mortality (2830).…”
Section: Discussionmentioning
confidence: 98%
“…Both cancer registry-based (1, 3, 1417) and non-registry based (18, 19) studies reported higher risk of overall mortality in diabetic breast cancer patients. Few studies have investigated the effects of diabetes on breast cancer-specific mortality; increased mortality was reported in two studies (18, 20), but not in a third study which also adjusted for BMI and other lifestyle factors (19). Our results strengthen the evidence that diabetes is associated with breast cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%